PERBANDINGAN PENINGKATAN HASIL BELAJAR EKONOMI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION LANGSUNG - Dede Kurniawan; Tedi Rusman; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
The results of the study is one of the indicators of the success of the purpose of learning. Research is aimed to ensure the effectiveness of the application of a model of learning cooperative type group investigation and the model of learning directly as if linked to the ability of early owned students in the subject economy. A model of learning cooperative type group investigation used in the classroom experiments and the model of learning directlyinto class of control. Methods used in this research is the experimental methods, exactly quasi experiment. The technique of sampling in this research is clusters of random sampling. The technique of collecting data done with the observations, documentation and engineering tests. (1) thus ho accepted which means there is a difference students study result of the economic model of learning through cooperative type group investigation and the model of learning directly.(2)thus ho accepted which means that there was increased study result of the economic between students who is given a model of learning cooperative type group investigaton with students who is given a model of learning directly. Kata Kunci: gi, langsung, hasil belajar